دراسة تحلیلیة لبعض فروق سمات الشخصیة بین طالبات كلیة التربیة الریاضیة (البنات -المستنصریة ) - علاء عبدالرضا حسين (physical education and sport sciences college for women/ Baghdad University, 2015)
The specialized to concur in human personality is thecornerstone for his development and progress in affirmative way also approximation between the two gender effect ,some to deem negativism others passivism the researcher consider study two different subjects of dealing with other gender .the interests of the search is personification weak and strength point in subjects of physical education students(girls- mustansryah ) using the list of (Freiburg)for personality.the aim of the study is to identify on some of personality traits)to study subject and the different between them ,the hypotheses of the study thersent any differentof personality traits between search subjectswhomconsist of (80) students distribute the list of (Freiburg) for personality to them. The searcher to reach that thersent any different of personality difference between search subjects and the searcher recommend to work on grow of personality traits to search subjects and necessary to procedures future studies on a bigger subjects